2018
DOI: 10.1089/dia.2018.0115
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Technologies for Diabetes Care

Abstract: New therapies, monitoring, and revolutionary enabling technologies applied to healthcare represent an historic opportunity to improve the lives of people with diabetes. These advances enable more meaningful monitoring of blood glucose values with the facilitation of more optimal insulin dosing and delivery. Newer insulins and delivery systems are in development that seek to mitigate both hyperglycemia and hypoglycemia and increase time in range. Information systems now exist that may be leveraged to merge data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 47 publications
0
49
0
Order By: Relevance
“…However, only a small proportion of participants entered their insulin doses as compared with BGL. Automation, such as the use of cloud-connected insulin pen devices, is likely to improve clinician access to data 14. Although the participants continued to have a few Bluetooth connectivity issues between the app and the glucose-meter, the majority of participants agreed that there were no technical problems using the system; this was an improvement on the proof-of-concept trial.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a small proportion of participants entered their insulin doses as compared with BGL. Automation, such as the use of cloud-connected insulin pen devices, is likely to improve clinician access to data 14. Although the participants continued to have a few Bluetooth connectivity issues between the app and the glucose-meter, the majority of participants agreed that there were no technical problems using the system; this was an improvement on the proof-of-concept trial.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, enhancement in treatment satisfaction may play a critical role in increasing patient self-efficacy and commitment to therapy, thereby supporting in reaching long-term stable glycemic control, in addition to the minimization of the risk of diabetic complications [18]. More recently, diabetes technology has extended, and studies reported that technological improvements in glucometers are enhanced diabetes management and patient satisfaction [19,[23][24][25]. In this present study, we explored whether the smartLIGHT™ based BGM can impact the clinical characteristics and GMS in T2D patients over a period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Bigfoot Biomedical is developing an insulin smart pen that will connect to the FreeStyle Libre system. It will be controlled with a mobile app and hopefully adjust long and short acting insulin doses without manual input [53].…”
Section: Smart Pen Systemsmentioning
confidence: 99%
“…Additionally, smartphone technology has decreased the cost and complexity of data sharing. The use of automated uploads from devices to the "cloud" has allowed both patient and physician to have almost real-time access to data [53].…”
Section: Mobile and Computer Applications (Apps)mentioning
confidence: 99%